A history of technical education in Ethiopia: The case of the Polytechnic Institute, 1963-2000 - Ayele, Fantahun (Bahir Dar Journal of Education, 2024)
This research aims at exploring and analyzing the history of the Polytechnic Institute from its establishment in 1963 to its transformation as the Faculty of Engineering in 2000. The study is mainly based on the consultation of priceless archival documents kept in the record office of the former Polytechnic Institute (now Bahir Dar Institute of Technology). In addition, attempts have been made to substantiate archival sources by gathering oral evidence from pertinent people including the first graduates of the Polytechnic Institute. The information gathered from archival documents (letters, reports, graduation bulletins, newspapers, etc.) and interviews has been carefully examined, cross-checked, interpreted, and analyzed to reconstruct the history of the institute. The findings of the study show that the Polytechnic Institute was the result of the Cold War rivalry between the two superpowers, the United States and the former Soviet Union. When the U.S. government turned down his request for increased military assistance, Emperor Haile Selassie paid an official visit to Moscow in 1959. Among other things, the Soviet government offered financial assistance that led to the establishment of the Bahir Dar Polytechnic Institute in 1963. The Soviet government also supported the institute by assigning technical advisers and instructors, whose number grew substantially after the 1974 revolution. The ideological solidarity between the two countries brought more scholarship opportunities to the students and instructors of the Institute. In 2000, the union of the Polytechnic Institute and Bahir Dar Teachers College gave rise to the birth of Bahir University. In the last sixty years, the Institute has produced world-class technologists.